Edukasi Tentang Menarche dan Terapi Relaksasi untuk Menurunkan Kecemasan dan Nyeri Saat Menstruasi pada Anak Sekolah Dasar - Mardiana Mardiana; Muhammad Basri (Jurnal Nusantara Berbakti, 2025)
Early menarche in elementary school children means that children need to have knowledge about menstruation from an early age. Knowledge about menstruation affects children's responses during their first menstruation and personal hygiene during menstruation, so children need correct information about menstruation. This community service aims to provide information about menstruation and complementary therapies, especially relaxation therapy to reduce anxiety and pain. There are four stages in implementing this education, namely the planning stage, preparation stage, implementation stage and monitoring and evaluation stage. There was an increase in students' knowledge after providing education. The results of this community service can show that providing education can increase students' knowledge.